2005
DOI: 10.2310/6350.2005.31307
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Comparative Evaluation of Three Laser Systems Used Individually and in Combination for Axillary Hair Removal

Abstract: At the 3-month follow-up, the long-pulse alexandrite and 810 nm diode lasers demonstrated no statistically significant differences in efficacy, comparable efficacy and tolerability, and highest subject satisfaction. Rotational therapy with the three laser systems is not as effective as treatment with the alexandrite laser or diode laser alone but is statistically more effective than use of the long-pulse Nd:YAG system alone. Individuals with red or light-colored hair and Fitzpatrick phototype II skin have decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
3
31
0
2
Order By: Relevance
“…The results 3 months after the last treatment session showed that diode (mean [SD], 59.3% [9.7%]) and alexandrite (58.7% [7.7%]) lasers offer maximum hair reduction, and the combination system offered the minimum result (31.9% [10.1%]). 12 These authors attributed the lesser effect of the combination It has been demonstrated that scattering of the laser beam is affected by the spot size. 13 One published study 14 of 3 treatments with an alexandrite laser in axilla showed a difference, although not statistically significant, of hair reduction for 18-vs 12-mm spot sizes (52% vs 42%) with the same fluence.…”
Section: Commentmentioning
confidence: 99%
“…The results 3 months after the last treatment session showed that diode (mean [SD], 59.3% [9.7%]) and alexandrite (58.7% [7.7%]) lasers offer maximum hair reduction, and the combination system offered the minimum result (31.9% [10.1%]). 12 These authors attributed the lesser effect of the combination It has been demonstrated that scattering of the laser beam is affected by the spot size. 13 One published study 14 of 3 treatments with an alexandrite laser in axilla showed a difference, although not statistically significant, of hair reduction for 18-vs 12-mm spot sizes (52% vs 42%) with the same fluence.…”
Section: Commentmentioning
confidence: 99%
“…18,19 Yet others have found no significant differences between them. 20,21 Previous studies have reported on the incidence of side effects. These have involved relatively few treatment episodes and patients.…”
Section: Comparison Of Efficacy and Adverse Effects Between The Lasermentioning
confidence: 98%
“…27 The scientific literature presents numerous reports on the effectiveness of LHR but is limited to different parts of the body and no reports on mixed-race participants have been found. 6,8,10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Objective The authors of this study have noticed that mixed-race patients' skin reacts differently than similar skin types according to the Fitzpatrick scale of non-mixed-race patients and so far no related research was found. The objective of the study was to investigate the occurrence and types of side and adverse effects after performing diode laser 805 nm hair removal in a group of mixed-race participants with phototypes III-V and to assess its impact on the results of the treatment measured as a percentage of hair reduction in the treated area.…”
Section: Introductionmentioning
confidence: 99%